Drohnentechnologie und moderne Kriegführung Bestandsaufnahme und Perspektiven - Balazünbül, Zeynep (Carl Grossmann Verlag, 2021)
Are armed drones a permissible and harmless military technology from the point of view of international humanitarian law? With this question, the author puts the much-discussed armed drones to the test of Article 36 of the First Additional Protocol to the Geneva Conventions, which imposes on states an obligation to test new weapons and means of warfare. Furthermore, the work deals with three controversial political theses around the effects of drone technology on modern warfare and explains what relevance these have from the perspective of international humanitarian law. The present work thus gives a complete view of the question of the admissibility of armed drones raised above.